1981
DOI: 10.3109/00498258109045851
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the epoxy resin component 2,2-bis[4-(2,3-epoxypropoxy)phenyl]propane, the diglycidyl ether of bisphenol a (DGEBPA) in the mouse.; Part II. Identification of metabolites in urine and faeces following a single oral dose of14C-DGEBPA

Abstract: 1. The major metabolic transformation of orally ingested 14C-DGEBPA is by hydrolytic ring-opening of the two epoxide rings to form diols. This metabolite (the bis-diol of DGEBPA) is excreted in both free and conjugated forms and is further metabolized to various carboxylic acids, including two containing a methylsulphonyl moiety. 2. The product of oxidative dealkylation either of DGEBPA (with concomitant formation of glycidaldehyde) or of the bis-diol of DGEBPA (with concomitant formation of glyceraldehyde) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…In addition to the direct intake of BADGE·2H 2 O from foods, in vivo metabolism of BADGE and other precursors can contribute to the formation of BADGE·2H 2 O in human bodies. 15,16,19,20 The proportion of BADGE·-H 2 O·HCl is relatively low, especially in urine from China, indicating a lower level of chloride derivatives of BADGEs in human urine. Creatinine also was determined in urine samples from the U.S. and China.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In addition to the direct intake of BADGE·2H 2 O from foods, in vivo metabolism of BADGE and other precursors can contribute to the formation of BADGE·2H 2 O in human bodies. 15,16,19,20 The proportion of BADGE·-H 2 O·HCl is relatively low, especially in urine from China, indicating a lower level of chloride derivatives of BADGEs in human urine. Creatinine also was determined in urine samples from the U.S. and China.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…15 According to the study, bisphenol A was one of the minor metabolites, and the amount was reported to be small. 16 The experiment by Climie et al used radiolabelled BADGE, so the results of their study seemed to be generally reliable.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we could not analyse major metabolites of BADGE, for example, bis-diol of BADGE, 15 because their standard reagents were not available. Thus, we could not directly confirm exposure to BADGE in the sprayers.…”
Section: Discussionmentioning
confidence: 99%
“…Both migrate from containers into foods, and are routinely ingested (Cabado et al 2008; Cao et al 2009). Studies of BADGE metabolism suggest that it is not a significant source of BPA (Climie et al 1981) although BPA leaches from some BADGE-containing dental sealants (Joskow et al 2006; Olea et al 1996). …”
mentioning
confidence: 99%